REDUCING INTRAVENTRICULAR HEMORRHAGE IN A LEVEL III NEONATAL INTENSIVE CARE UNIT. Issue 11 (22nd October 2015) - Christ, Lori; Barber, Jessica; Murray, Ashley; Dunleavy, Melissa; Stoller, Jason; Taha, Dalal; Brown-Jackson, Loretta; McElroy, Meredith; Posencheg, Michael
Abstract : Background: Intraventricular hemorrhage (IVH) is a common complication of prematurity and has been associated with adverse short and long term outcomes. Despite the identification of risk factors for IVH, the overall rate has remained stable during the last decade. Objectives: Our aim was to reduce the incidence of severe IVH in preterm infants (<30 weeks) in our NICU from 8% to 4% between October 2014 and December 2015. Methods: A multidisciplinary team drafted a charter using the Model for Improvement (fig 1). Implementation began in October 2014. Ongoing interventions include: midline head positioning (MHP) during the first week of life, a minimal handling bundle inclusive of a multidisciplinary admission huddle (fig 2), increasing IVH awareness using a web-based risk calculator (www.neoqic.org/sivh-calculator), and standardizing infusion rates for boluses/blood products. Outcome measures include number of severe and overall IVH by birth month and fiscal year rate (%). Process measures include compliance with MHP and admission huddle (%), and discussion of IVH risk (%). Balancing measure is the rate of unplanned extubation. Results: The average monthly rate of severe IVH has decreased from 8.3% in FY14 to 5.1% in FY15 (fig 3). We report 227 days and 37 infants <30 weeks without severe IVH despite infants with similar IVH risk during the intervention period. MHP and admission huddle compliance for infants <30 weeks have recently reached 100% (fig 4). Conclusions: By implementing potentially better practices, we have measurably reduced severe IVH. Future directions include delayed cord clamping, prophylactic indomethacin for IVH prevention, and reviewing IVH cases with providers.Figure 1 Figure 2 Figure 3 Figure 4